2016
DOI: 10.1111/ijcp.12783
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of solifenacin therapy in patients with overactive bladder in the clinical setting: a prospective, multicenter, observational study

Abstract: There was low persistence (22%) to solifenacin therapy for OAB symptoms over a 12-month period. Older patients, female patients and those with fewer episodes of nocturia were more persistent to therapy than were others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…In this study, we found that 45.4% patients discontinued the FDC medication within 6 months. This finding was similar to that in previous Korean studies evaluating treatments for other urologic conditions, including LUTS/BPH and overactive bladder [15][16][17]. However, this finding was much lower than that in previous western studies evaluating treatment persistence with once-daily tadalafil for ED [18].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we found that 45.4% patients discontinued the FDC medication within 6 months. This finding was similar to that in previous Korean studies evaluating treatments for other urologic conditions, including LUTS/BPH and overactive bladder [15][16][17]. However, this finding was much lower than that in previous western studies evaluating treatment persistence with once-daily tadalafil for ED [18].…”
Section: Discussionsupporting
confidence: 87%
“…Lee et al [ 53 ] reported that only 25% of men with benign prostatic obstruction and OAB remained on their solifenacin add-on therapy after tamsulosin monotherapy within one year in a real clinical environment. Kim et al [ 54 ] also reported that 1-year persistence on solifenacin was 22.1% in a prospective, multicenter, observational study conducted in Korea. In their study, persistence at 12, 24, and 36 weeks was 72.4%, 45.8%, and 31.1%, respectively.…”
Section: Persistence and Compliance Among Patients Receiving Pharmacomentioning
confidence: 99%
“…In a postal-based survey conducted in the United States, 24.5% of patients who had been prescribed antimuscarinics for OAB reported that they had discontinued one or more antimuscarinic prescription medications during the previous 12 months [ 29 ]. In other open-label observational studies, the rates of medication discontinuation in 12 months were 21% to 78% of those taking antimuscarinics [ 27 51 52 53 54 ]. In a multicenter, prospective, and observational study conducted in Korea [ 27 ], 56.8% of patients with OAB remained on their antimuscarinics at 24 weeks.…”
Section: Persistence and Compliance Among Patients Receiving Pharmacomentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies that included persistence for at least one of the treatments evaluated in table or graph form were selected. 8,12,[20][21][22][23][24][25][26][27][28][29][30][31] We did a multiple comparison treatment from real world evidence persistence studies. The results were weighted according to the sample size for each treatment, taking into account the time frame for each study.…”
Section: Probabilitiesmentioning
confidence: 99%